Mechanical performance in axial compression of a titanium polyaxial locking plate system in a fracture gap model - Tomlinson, A. W.; Comerford, E. J.; Birch, R. S.; Innes, J. F.; Walton, M. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objective: To evaluate the bending strength of the VetLOX® polyaxial locking plate system.Materials and methods: Thirty-five 3.5 mm 12-hole titanium VetLOX® plates were used to stabilize seven different construct designs in a 1 cm fracture gap simulation model. Each construct was subjected to axial compression. Mean bending stiffness (BS) and yield load (YL) of each construct design were analysed using a one-way ANOVA and Tukey post-hoc analysis. Screw angulation was measured on reconstructed computed tomography (CT) images.Results: Reducing plate working length for fixed-angle constructs significantly increased BS (p <0.01) and YL (p <0.01). For a constant plate working length, increasing screw number did not significantly affect BS (p = 1.0) or YL (p = 0.86). Screw angulation measurement technique was validated by intra-class correlation coefficients (ICC) (ICC >0.9 for inter- and intra-observer measurements). An average screw angle of 13.2° did not significantly affect mechanical performance although incomplete screw head-plate engagement was noted on some reconstructed CT images when angulation exceeded 10°. Prefabricated screw-head inserts did not significantly increase mechanical performance. A 4 mm bone-plate stand-off distance significantly reduced BS and YL by 63% and 69% respectively.Clinical relevance: The VetLOX® system allows the benefits of polyaxial screw insertion whilst maintaining comparable bending properties to fixed angle insertion. The authors recommend accurate plate contouring to reduce the risk of plate bending.
Keywords: VetLOX; polyaxial; locking plate; Delrin rods; screw angulation